Effects of oven temperature and addition of ethanol on measurement of water content and specific gravity of cement-stabilized soft clay - Yu, Hua (2021)
Water content and specific gravity are two fundamental soil properties. The water content is usually measured by the oven-drying method, and the dried soil is used for specific gravity determination of the soil. However, for cement-stabilized soils, high oven temperature accelerates the cement hydration rate and causes dehydration of some clay minerals, which may affect the measurement accuracy of water content and soil specific gravity. Hence, researchers have proposed the use of ethanol to terminate cement hydration reactions and a low oven temperature to reduce the dehydration of hydration products. To verify the effectiveness, this experimental study investigated the effects of oven temperature (60°C and 110°C) and the addition of ethanol on the measurements of both water content and specific gravity of cement-stabilized soft clay. These measurements are compared with those measured with the freeze-drying method, which is termed as a control measurement. The test results indicated that the effect of ethanol on water content measurement was insignificant. For 7-day stabilized clay, oven drying at 110°C achieved lower errors (3.06-3.63 %) than the oven-drying method at 60°C (7.36-9.44 %). For 180-day cement-stabilized clay, all the oven-drying methods had similar measurement errors (4.02-5.58 %). The effect of drying method on the specific gravity measurement was insignificant, with the percentage of measurement error ranging from 0.19 to 2.17 %.